Diversity of Cellulolytic Microbes and the Biodegradation of Municipal Solid Waste by a Potential Strain - S. P. Gautam; P. S. Bundela; A. K. Pandey; Jamaluddin; M. K. Awasthi; S. Sarsaiya (International Journal of Microbiology)
Municipal solid waste contains high amounts of cellulose, which is an ideal organic waste for the growth of most of microorganism as well as composting by potential microbes. In the present study, Congo red test was performed for screening of microorganism, and, after selecting a potential strains, it was further used for biodegradation of organic municipal solid waste. Forty nine out of the 250 different microbes tested (165 belong to fungi and 85 to bacteria) produced cellulase enzyme and among these Trichoderma viride was found to be a potential strain in the secondary screening. During the biodegradation of organic waste, after 60 days, the average weight losses were 20.10% in the plates and 33.35% in the piles. There was an increase in pH until 20 days. pH however, stabilized after 30 days in the piles. Temperature also stabilized as the composting process progressed in the piles. The high temperature continued until 30 days of decomposition, after which the temperature dropped to 40°C and below during the maturation. Good quality compost was obtained in 60 days.